TELAAH KRITIS KEBIJAKAN PENANGGULAN KEMISKINAN DALAM TINJAUAN KONSTITUSI - - Multifiah (Journal of Indonesian Applied Economics, 2011)
This paper aims to examine several poverty alleviation programs which have beendone for periods of time and evaluate the programs constitutionally in the frameworkof UUD 1945. The study finds that there are many programs held by the government,yet their mostly obstacles are overlapping objectives and the problem of corruptionand collusion. Moreover, the absence of clear guidance makes the conditions worse.UUD 1945 focuses in how to reduce poverty through basic needs fulfillment such aseducations, health, and social safety net, which are needed as key ingredients to suc-ceed sustainable poverty alleviation programs.Keywords: poverty alleviation programs, UUD 1945.